A novel high-throughput and quantitative method based on visible color shifts for screening Bacillus subtilis THY-15 for surfactin production. (1st August 2015) - Yang, Huan; Yu, Huimin; Shen, Zhongyao
Abstract: A novel chromatic visible screening method using bromothymol blue (BTB) as a color indicator and cetylpyridinium chloride (CPC) as a mediator was constructed to obtain the high titer surfactin-producing strains. The reliability and quantification accuracy of color shift were also confirmed. Regular chromatic responses from faint yellow-green to dark green and bright blue reflected the different ranges of surfactin concentrations. Moreover, the quantitative accuracy of surfactin quantification in the range of 100–500 mg/L was verified by reverse-phase high-performance liquid chromatography (RP-HPLC) using different fermentation supernatant samples. Using this CPC–BTB method, a superior surfactin producer, Bacillus subtilis THY-15, was successfully screened. The producer's surfactin (Srf) titer reached 1240 mg/L. RP-HPLC analysis of THY-15 revealed four surfactin isoforms. As identified by amino acid analysis and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry analysis, the isoforms of surfactin in fraction 1, 2 and 4 had the same circular peptide sequence of Glu-Leu-Leu-Val-Asp-Leu-Leu but different iso-C13, C14 and C15 fatty acid chains, but the isoform in fraction 3 possessed a special peptide sequence of Glu-Val-Leu-Leu-Asp-Leu-Val.